Analisis Kelebihan dan Kekurangan dalam Teknik Animasi Comic Book Look pada Animasi “Arcane” - Indra Febrianto Nugroho (Peneliti.net, 2023)
3D animation is currently on the rise in modern cinema circles lately. Coupled with online streaming platforms, access to watching movies from home is even easier. One of the well-known 3-D animations and won the best animation award in 2022 is the animated series